Faktor Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Tenaga Kerja Bongkar Muat (TKBM) Unit Pengantongan Pupuk di Pelabuhan Tanjung Emas Semarang Tahun 2022 - Oky Noor Diansyah; Bayu Yoni Setyo Nugroho (Journal Occupational Health Hygiene and Safety, 2023)
When a person experiences fatigue due to work, the body’s physical and mental abilities tend to decrease which causes workers to be less careful when working. Fatigue due to work contributes 50% to work accidents. The purpose of this study was to analyze the relationship between age, nutritional status, length of work and workload with work fatigue in the loading and unloading workers at the Fertilizer Packing Unit at Tanjung Emas Port Semarang.This research is a quantitative research with a cross sectional design. Fatigue data was collected using a reaction timer, workload was measured using a Nasa- TLX questionnaire, nutritional status was measured using a weight scale dan microtoise , while age and years of service were measured using a questionnaire. The sample in this study amounted to 58 morning shift respondents who were taken with a simple random sampling method. Data analysis using Rank Spearman Test Based on the result of univariate analysis, it is known that the majority of respondents are 36-49 years old (43,1%). The most nutritional status was obesity, which amounted to 48,3%, some respondents had worked less than 15 years (55,2%). Most of the respondents experienced a high workload of 60,3%, the majority of respondents experienced work fatigue, heavy work fatigue with a total of 72,4%. Based on the results of the Rank Spearman test, there is a relationship between age and work fatigue with a result of p=<0,001, there is no relationship between nutritional status and work fatigue with a result of p=0,231, there is a relationship between work period and work fatigue with a result of p=<0,001, there is a relationship between workload with work fatigue with the result p=<0,001.